Importance of early physical rehabilitation in improving functional state of vegetative nervous system of women with postmastectomy syndrome - Odynets, Tatiana; Briskin, Yuriy (Slobozhanskyi Herald of Science and Sport, 2016)
Purpose: to determine the expediency of early application of physical rehabilitation to improve the functional state of vegetative nervous system of women with postmastectomy syndrome. Material & Methods: theoretical analysis of scientific and methodical literature, analysis of heart rate variability, methods of mathematical statistics. The study involved 135 women with postmastectomy syndrome who underwent radical mastectomy for Madden. Results: at the end of the research value of high-frequency component of the spectrum was significantly higher in women MG1 compared to MG on 257,72 ms² (p<0,01) and the stress index was lower on 107,01 c. u (p<0,001). Conclusions: the feasibility of early rehabilitation intervention to improve the functional state of the autonomic nervous system is not detected during the year classes on problem-oriented programs.